Gallbladder Mucocele: Variables Associated with Outcome and the Utility of Ultrasonography to Identify Gallbladder Rupture in 219 Dogs (2007–2016). (4th December 2017) - Jaffey, J.A.; Graham, A.; VanEerde, E.; Hostnik, E.; Alvarez, W.; Arango, J.; Jacobs, C.; DeClue, A.E.
Abstract : Background: Gallbladder mucocele (GBM) is an increasingly recognized extrahepatic biliary disease in dogs. Objectives: To investigate cases of GBM and identify variables associated with survival and the sensitivity and specificity of ultrasonography to identify gallbladder rupture. Animals: Two hundred and nineteen client‐owned dogs with GBM. Methods: Multicenter, retrospective study of dogs with GBM, presented from January 2007 to November 2016 to 6 academic veterinary hospitals in the United States. Interrogation of hospital databases identified all cases with the inclusion criteria of a gross and histopathologic diagnosis of GBM after cholecystectomy and intraoperative bacteriologic cultures of at least 1 of the following: gallbladder wall, gallbladder contents, or abdominal effusion. Results: Two hundred and nineteen dogs fulfilled the inclusion criteria. Dogs with GBM and gallbladder rupture with bile peritonitis at the time of surgery were 2.7 times more likely to die than dogs without gallbladder rupture and bile peritonitis ( P = 0.001; 95% confidence interval [CI], 1.50–4.68; n = 41). No significant associations were identified between survival and positive bacteriologic cultures, antibiotic administration, or time (days) from ultrasonographic identification of GBM to the time of surgery. The sensitivity, specificity, positive, and negative likelihood ratios for ultrasonographic identification of gallbladder rupture were 56.1% (95% CI, 39.9–71.2), 91.7% (95% CI, 85.3–95.6), 6.74, and 0.44, respectively. Conclusion and Clinical Importance: Dogs in our study with GBM and intraoperative evidence of gallbladder rupture and bile peritonitis had a significantly higher risk of death. Additionally, abdominal ultrasonography had low sensitivity for identification of gallbladder rupture.